Evaluation of efficacy of chicken egg yolk (IgY) antibodies and aloe vera extract against Candida albicans in vitro and In vivo with respect to oral candidiasis - Dr.T.JEEVITHA; Dr.K.DEEPA; Dr.A.MICHAEL (International Journal of Pharma and Bio Sciences, 2019)
The present research work was aimed to produce chicken egg yolk antibodies against the whole cell antigen of Candida albicans, to prepare Aloe vera extract and to test their potential both in vitro and in vivo to control the virulence and development of the fungi. The anti-C.albicans IgY was tested for its efficacy to inhibit the cell growth of C.albicans by growth inhibition assay. The growth of C.albicans with specific IgY showed significant reduction when compared with unimmunized IgY. The ability of anti C.albicans IgY and Aloe vera extract to inhibit the adhesion of C.albicans to KB cell lines was evaluated by adhesion inhibition assay since adhesion is the first prerequisite condition required for C.albicans to induce infections. Our results indicated that they could efficiently inhibit the adherence of C.albicans to the KB cells which were significantly (P<0.05) higher when compared with the unimmunized IgY treated group. Further, the efficacy of anti-C.albicans IgY and Aloe vera extract were evaluated in immunosuppressed mice models. Both of them were able to show significant impact on relative body weight of the infected mice, reduced the tongue lesions and showed lesion score which were significantly less when compared with the unimmunized IgY treated group. They showed an effective reduction of the C.albicans load in the mice challenged with the inoculums from the oral swab. Our results revealed that the fungal load was significantly reduced in anti C.albicans IgY and Aloe vera extract treated group when compared with unimmunized IgY treated group in histopathological examination. With these findings it is suggested that IgY antibodies and Aloe vera extract could be used as a prophylactic measure against oral candidiasis in the form of different oral care products such as lozenges, chewing gum and mouth rinses.